THE IMPORTANCE OF HERPESVIRUSES IN THE ETIOLOGY OF A NUMBER OF INFECTIOUS AND SOMATIC DISEASES OF CHILDREN - T. N. Rybalkina; N. V. Karazhas; P. A. Savinkov; R. E. Boshyan; M. Y. Lysenkova; M. N. Kornienko; P. A. Veselovsky; E. M. Burmistrov; T. M. Lebedeva; P. A. Markin (LLC "Diagnostics and Vaccines", 2017)
The article is devoted to study the etiological role of herpes viruses in infectious and somatic pathology of children (n = 770) using the complex of methods of laboratory diagnostics. Determined the leading etiological role of HSV in children with neuroinfections (12,7%) during primary infection and in children with intrauterine infection (29,0%) during its reactivation. It is shown that in 50,9% of cases, the diagnosis of «infectious mononucleosis» confirmed by the detection of markers of acute EBV-infection, and 20,0%, it was replaced by mononucleotides syndrome was discovered markers of acute CMV-infection, and 18,1% - markers of acute HHV-6-infection. The role of HHV-6 as the primary etiologic agent of the disease is established at 36,3% of children admitted with convulsive syndrome on the background of febrile, at 29,1% - a sudden exanthema and 25,5% - with fever of unknown origin.